Drug utilization patterns in the global context: A systematic review. Issue 4 (December 2017) - Atif, Muhammad; Scahill, Shane; Azeem, Muhammad; Sarwar, Muhammad Rehan; Babar, Zaheer-Ud-Din
Abstract: Objectives: Standard drug use indicators have been developed by the World Health Organization/International Network for Rational Use of Drugs (WHO/INRUD). The purpose of this systematic review was to examine and report the current status of health facilities in different regions of the world in terms of drug use based on WHO/INRUD core drug use indicators. Design: Systematic review of the literature following PRISMA guidelines. Methods: The INRUD bibliography, WHO archives, Google Scholar, Medline, PubMed, SpringerLink, ScienceDirect and Management Sciences for Health (MSH) resource databases were searched between 1985 and 2015 for studies -containing 12 WHO/INRUD core drug use indicators. Secondary data sources were also searched. Results: Four hundred and sixty three studies were retrieved and 398 were excluded as they did not provide relevant information or fulfill the selection criteria. Sixty articles met the criteria and were selected for final review. With respect to prescribing indicators, studies of "drug use" showed mixed patterns across geographic regions. Overall trends in "patient-care" and "facility-specific" indicators were similar across most of the World Bank regions. However, based on the Index of Rational Drug Use (IRDU) values, East Asia and the Pacific region demonstrated relatively better drug use practices compared with other regions. Conclusions: This systematic review revealed that the drug use practices in all regions of the world are suboptimal. A regulated, multi-disciplinary, national body with adequate funding provided by governments throughout the world are a basic requirement for coordination of activities and services, to improve the rational use of drugs at a local level. Highlights: Average number of drugs per prescription met optimal levels for all World Bank regions except Latin America and the Caribbean. Improvement needed in percentage of antibiotics prescribed per prescription in all regions of the world. There is no country where the percentage of drugs prescribed by generic name is at optimal levels. Average consultation time of physicians was below the optimal value (≥10 minutes) except for Europe and Latin America. The percentage of drugs dispensed and availability of essential drugs was close to optimal except in Europe and Latin America.